Job Crafting and Work Engagement: A Scientometric Mapping of Global Research Trends and Future Directions - Aidilla Qurotianti; Rini Juni Astuti (SAFE-Network, 2026)
This study conducted a global scientometric mapping of research related to job crafting and work engagement using data from the Scopus database. The main focus is on identifying publication trends, scientific collaborations between authors, institutions, and countries, as well as thematic clusters that dominate the literature on these two key concepts. The bibliometric analysis reveals the rapid development of research from 2015 to 2025 which is influenced by the dynamics of the modern work environment such as digitalization, remote work, and organizational paradigm changes after the COVID-19 pandemic. Job crafting is seen as a proactive behavior that is an important mechanism in increasing work engagement as well as various positive consequences such as performance, job satisfaction, and employee well-being, while anticipating the risk of burnout and work burnout. Five main thematic clusters were found, namely: the relationship between job crafting and work output, the role of work resources and motivation, crafting careers and well-being, the influence of leadership on performance, and health and work environment support. An integrative conceptual framework was developed that places work engagement as the main mediator that connects work, organizational, and individual antecedents with work outcomes, with contextual factors as moderators. This research provides a comprehensive overview of intellectual development and future research directions that are important for academics and practitioners in the field of human resource management.